Ontology-based engineering for self-managing communications - FEENEY, KEVIN; KEENEY, JOHN; LEWIS, DAVID; O'SULLIVAN, DECLAN; POWER, RUAIDHRI SEAN (multicon verlag, 2006)
Ontology-based semantics support encoding and mapping between separately authored and thus heterogeneous knowledge, and is expressed in widely accepted standards (e.g. W3C?s OWL). It has been suggested that ontology-based semantics will bring benefits to the management of a diversity of systems, ranging from conventional communication services to future autonomic communication services. This paper examines the state of the art in the application of ontological modeling to a range of concerns of interest in the engineering of communication services. In particular the role of ontology modeling for the modeling of services, policies, context, management information and semantic mappings will be examined.
PUBLISHED
Keywords: Computer Science